Contributions of Indian Scholars to Arabic Fiqh Literature: A Medieval historical perspective - Alom , Jahangir (International Journal of Psychosocial Rehabilitation, 2020)
The fiqh is a legislation laid down by religion to perform the complete practice of Islam. As Islam spread in the new areas of the world, people faced numerous problems in practicing religious rituals due to the geographical and climatic differences in the new areas. There required a new laws and fatwas to meet the new problems regarding religious practices of Islam. Hence the diverse Islamic laws concerning social, religious and political aspects had to come up with changes and modifications for the requirements of time and place. In medieval era the Arabic knowing scholars of India endeavours to contribute to the works on fiqh or religious ordinance which laid down by Islam and not comprised all the aspects of social, criminal, civil, political as well as financial phenomena as a whole. These scholars contributed a lot in framing new legislations in the non-Arabic speaking counties like India. They made remarkable outputs in the field of Jurisprudence in Arabic language, Persian as well as in Urdu. The immigrant Muslim scholars also have great contributions and were the leading scholars who spread the new ideas and knowledge in field of literature in India. The paper encompasses the eminent Indian Arabic scholars and their outstanding machinery in the field of Arabic Fiqh literature.